Prediction of surface leakage current of overhead insulators under environmental and electrical stresses - F. S. Abdullah; M. A. M. Piah; N. A. Othman; A. Din (Bulletin of Electrical Engineering and Informatics, 2020)
Leakage current is one of the critical aspects to consider for overhead transmission line insulator’s condition and performance assessment. As the leakage current increase, the size of the dry band also will increase leads to the dry band arcing, deteriorate the insulator performance and contribute to the development of insulator flashover. Based on the literature study, other than the existence of contaminations on the surface of insulator combined with moisture, the variation in leakage current is also affected by the environmental and electrical stresses. Previous researches have shown the effect of environmental and electrical stresses on surface leakage current based on experimental and simulation results. This paper outlines an analytical approach based on dimensional analysis to propose a new mathematical model of leakage current under environmental and electrical stresses. To justify the applicability of the derived dimensional model, the new model has been validated using previous researcher’s experimental results. The validation indicated that the proposed model had shown a good agreement with the previous experimental results. The proposed dimensional equation for this research work can be potentially used as a predictive performance model to evaluate and monitor the leakage current and insulator’s performance